A Medical Centrifuge System Based on the Switched Reluctance Motor - Nurettin USTKOYUNCU; Osman EROGUL (Gazi Üniversitesi Fen Bilimleri Dergisi, 2018)
A prototype medical centrifuge system based on switched reluctance motors (SRMs) is designed and realized in this study. Although medical centrifuge systems use asynchronous motors or motor structures with permanent magnets in general, an SRM had many advantages compared to other types of electrical motors is designed and used as a drive motor in the study. A driver unit to operate the system under desired conditions and all mechanical components are designed and manufactured in the study. Therefore, the study shows that the cost effective medical centrifuge systems can be produced with different technological specifications.